Evaluasi efek samping obat pada pasien rawat inap di Rumah Sakit “X” di Jakarta - Iyan Hardiana; Ivans Panduwiguna; Aji Abdaul Mujaki; Jerry Jerry; Taufani Taufani (Health Sciences and Pharmacy Journal, 2022)
One of the problems related to the use of drugs is the presence of side effects of drugs. Side Effects Drugs are responses to a drug that is detrimental and undesirable and that occur at doses typically used in humans for the prevention, diagnosis, or therapy of diseases or the modification of physiological functions. Side effects in drug administration are unexpected effects that can arise in treatment. This study aims to determine the number of Side Effects of Drug incidences and what drugs cause Side Effects of the Drug on inpatients at "X" Hospital Jakarta. The research method was descriptive non-experimental research by taking data using retrospective methods. The results of the study showed as many as 139 cases that were suspected of experiencing Adverse Drug Reactions with the number of drug side effects events with a Naranjo score scale of 9-13 must have occurred Adverse Drug Reactions obtained by one patient who experienced Adverse Drug Reactions, then the Naranjo score scale of 4 - 8 most likely Adverse Drug Reactions as many as 86 cases with a percentage of 61.87%, then with a Naranjo score scale 1 - 3 The possibility of Adverse Drug Reactions occurring as many as 52 points with a guarantee of 37.41%.  The class of drugs suspected of causing drug side effects are antibiotics, with as many as 86 cases (61.87%). The drugs suspected of causing drug side effects are ciprofloxacin, as many as ten items (7.19%), and levofloxacin, ten items (7.19%), the form of manifestation of drug side effects was the highest form of Side Effects of the Drug, namely with redness symptoms as many as 33 cases (23.74%). The drugs given to overcome Side Effects of the Drug are dexamethasone 58 drug items (41.73%); these results showed that a high probability of Side Effects of the Drug in patients staying at X Jakarta hospital was still high. It needs to be re-evaluated for its use